RESPONSE OF PHOSPHORUS AND MOLYBDENUM ON YIELD AND QUALITY ATTRIBUTING CHARACTERS OF INDIAN MUSTARD (BRASSICA JUNCEA L. CZERN & COSS) - K. C. VERMA; M. A. BAIGH (The Bioscan, 2012)
The oilseeds scenario in India has undergone a significant change in recent years. Present study suggests that increasing doses of P (upto 60kg/ha) and Mo (upto 4kg/ha) directly influence the yield and yield attributing parameters of mustard. Significant correlation was observed among number of siliquae per plant, Primary/ Secondary/ Tertiary branches, No. of siliquae/ No. of seed per siliqua, yield and oil content by different doses of P and Mo. P and Mo levels did not affect Siliqua length, Protein content and other biochemical characters significantly. Among fatty acids saturated fatty acids varies between 3.11-4.10%, whereas, unsaturated fatty acids between 4.32-48.45%.